Management and administration of higher education institutions at times of change - Visvizi, Anna; Lytras, Miltiadis D.; Sarirete, Akila (Emerald studies in higher education, innovation and technology., 2019)
As a new model of growth and development comes into force, higher education institutions (HEI) worldwide have to adapt and respond to a constantly changing environment. Politics, economics, advances in technology and the resultant societal change create a number of opportunities and challenges that HEI' administrators have to address on a daily basis. This volume offers practice-driven accounts of how HEI successfully embrace these challenges and opportunities.The experts and practitioners contributing to this volume reveal a complex reality of HEI today. The book links the debate on education to topical issues in politics, society and economy, including questions of technological progress, social responsibility, sustainability, well-being and, broadly understood, resilience. The authors emphasise the importance of the role of the university in supporting new models of growth by ensuring that the institutions strive towards inclusive education for all. Topics examined in this timely book include university social responsibility, emerging technologies in Higher Education and digital games-based learning and organizational innovation, in a range of international contexts.Given its practice-drive approach, this book will be invaluable for researchers, administrators and leaders in higher education management.